QUANTUM COMPUTING IN DATA ENCRYPTION: THE NEXT FRONTIER FOR SECURE DIGITAL COMMUNICATION - Dr. Luis Rodriguez (Modern American Journals, 2025)
As the world becomes increasingly interconnected, the demand for secure digital communication is more crucial than ever. Traditional cryptographic techniques, such as RSA and AES, have long been the backbone of secure data encryption. However, with the advent of quantum computing, the future of cryptography is undergoing a fundamental shift. Quantum computers have the potential to break widely used encryption schemes, posing a significant challenge to cybersecurity. This paper explores the role of quantum computing in the field of data encryption, analyzing both the risks posed by quantum computing to current cryptographic methods and the emerging quantum-resistant algorithms. The paper also examines the concept of quantum key distribution (QKD) and its potential to revolutionize secure communication. By discussing the progress of quantum computing and quantum cryptography, this paper aims to provide a comprehensive understanding of how quantum technologies are set to impact the future of secure digital communication.
Keywords: Quantum Computing, Data Encryption, Cryptography, Quantum Key Distribution, Quantum-Resistant Algorithms, Digital Communication, Cybersecurity, RSA, AES, Post-Quantum Cryptography, Secure Communication, Cryptographic Algorithms.